Women with Premenstrual Dysphoric Disorder experiences of suicidal thoughts and behaviours: a mixed methods study - Brown, Danielle; Smith, Debbie M.; Osborn, Elizabeth; Wittkowski, Anja (Frontiers in Psychiatry, 2024)
Background Women with Premenstrual Dysphoric Disorder (PMDD) experience debilitating psychological symptoms during each luteal phase of their menstrual cycle. Although women’s increased risk of suicidal thoughts and attempts to end their lives has been highlighted, little is as yet known about women’s own narratives. Therefore, this study aimed to explore the prevalence and the experiences of self-harm, suicidal thoughts and attempts in women with PMDD. Method In this mixed methods study, women’s experiences of living with PMDD were captured via an online survey exploring risk and via semi-structured interviews with questions informed by survey results. Data were analysed using descriptive statistics and reflexive thematic analysis. Results Over 3,600 women completed the survey between January and March 2020 and 14 women were subsequently interviewed in 2022. The survey revealed that just under half of women had deliberately harmed themselves during a PMDD crisis, 82% had suicidal thoughts on one or more occasions during their luteal phase, and 26% of women had attempted to end their own life. Three main themes, which related to suicidal ideation in the context of PMDD, were generated from the interview data: 1) personal relationships and social connections affected by PMDD, 2) the increase in suicidal experiences caused by diagnosis delays and 3) self-worth damaged by PMDD. Conclusion Women living with PMDD are at high risk of self-harm, suicidal thoughts and attempts to end their lives each month, narratives highlighted the damaging impacts PMDD had on relationships. Risk was increased by delays in appropriate medical support and women reported internalising their experiences as their problem.